Identifikasi Tungau Debu Rumah di Tempat Tinggal Pasien Dermatitis Atopik RSUD Petala Bumi Pekanbaru - Suri Dwi Lesmana; Deon Pradana Putra; Alida Widiawaty (Jurnal Ilmu Kedokteran, 2018)
House dust mite have an important role as an allergens in allergic diseases such as atopic dermatitis. Atopic dermatitis is inflammation of the skin with itching, chronic and recurrent symptoms. The aim of this study was to find out the description of house dust mites in the house of patients at Petala Bumi Hospital. Design of study was a crosssectional. This study was occured from May-June 2018 in the Laboratory of Parasitology and involved 30 atopic dermatitis patients with consecutive sampling technique. Results is showed 100% of atopic dermatitis patients house were positive for house dust mites, 63.3% of patients behaved badly in hygiene which affected degree of house dust mite spread. Conclusions of this study showed that a whole place of atopic dermatitis patients house was positive for house dust mite, most of patients behaved badly in hygiene which affected degree of house dust mite spread.